2016
DOI: 10.26719/2016.22.9.682
|View full text |Cite
|
Sign up to set email alerts
|

The status of serum vitamin D in the population of the United Arab Emirates

Abstract: Research exploring the status of serum vitamin D levels in the populations of countries bordering the Arabian Gulf shows a high prevalence of vitamin D deficiency/insufficiency. These reports were usually drawn from small samples unlikely to be representative of the population. We explored serum vitamin D level in a large sample (7924) of patients who were given a blood test to check their vitamin D status on their first consultation at a day surgery hospital in Dubai. The overall mean level of 25(OH) D was ~ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…In the current study, Qatari nationality (local population) had the highest rate of severe deficiency (18.9%) compared with other nationalities (12.3%). The UAE study showed a statistically significant lower mean vitamin D level (19.1 ng/mL) among the local population compared with expatriates (20.07 ng/mL) 16. The type of dress covering the whole body (in females as well as males) may explain such a difference.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the current study, Qatari nationality (local population) had the highest rate of severe deficiency (18.9%) compared with other nationalities (12.3%). The UAE study showed a statistically significant lower mean vitamin D level (19.1 ng/mL) among the local population compared with expatriates (20.07 ng/mL) 16. The type of dress covering the whole body (in females as well as males) may explain such a difference.…”
Section: Discussionmentioning
confidence: 89%
“…Another systematic review found that severe vitamin D deficiency (<10 ng/mL) was most common in South Asia and the Middle East 22. The prevalence of vitamin D deficiency in UAE was 85.4% 16. In another study from Saudi Arabia conducted on adult males aged 20–74 years old, 87.8% had vitamin D level <20 ng/mL 11.…”
Section: Discussionmentioning
confidence: 99%
“…We surveyed local and international undergraduate students in Dubai and assessed their vitamin D-related knowledge and habits, as well as their perceived health status. Vitamin D deficiency is epidemic in the UAE, in both genders, in both local and non-local populations, and especially in the 17-31 years' age group (Yammine and Al Adham, 2016;Baniissa et al, 2017;Al Zarooni et al, 2019;Al Amiry and Shahwan, 2020). It is well documented that primary sources of vitamin D include exposure to UV rays, supplementation, Very Poor (%) 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 and diet (Giustina et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few lines of evidence suggest a low knowledge regarding the health implications of vitamin D deficiency, coupled with a low testing rate and avoidance of vitamin D supplementation (Al Anouti et al, 2011;Salmanpour et al, 2016;Ibrahim and Al-Tameemi, 2019). Hence, the reports of an epidemic of vitamin D deficiency among Emiratis and residents of the UAE (Yammine and Al Adham, 2016;Bani-issa et al, 2017;Al Zarooni et al, 2019;Al Amiry and Shahwan, 2020), with a prevalence reaching 85% in some reports (Yammine and Al Adham, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is an insufficient knowledge among young populations with a high prevalence of VDD despite living in sunny areas like UAE, Saudi Arabia, and India [6][7][8][9][10] .…”
Section: -Hydroxyvitamin D [25(oh)d]mentioning
confidence: 99%